2022
DOI: 10.1364/oe.473853
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a null test for freeform optics using a high-definition spatial light modulator

Abstract: We report the implementation of an interferometric null test using a high-definition spatial light modulator (SLM) as a reconfigurable alternative to a computer-generated hologram. We detail the alignment process chain, including novel techniques using the SLM to project alignment fiducials on the test part. To validate the alignment protocol, we measure a mild off-axis conic with the SLM-based system and cross-validate with conventional interferometry within 30 nm root-mean-square (RMS) surface figure. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Minimizing the phase ripple of the SLM is critically important in applications including cold atom trapping 17 and interferometry 18 . As discussed in section 3.1, operating the SLM at an elevated temperature increases the response time of the liquid crystal molecules.…”
Section: Optimizing Phase Ripplementioning
confidence: 99%
“…Minimizing the phase ripple of the SLM is critically important in applications including cold atom trapping 17 and interferometry 18 . As discussed in section 3.1, operating the SLM at an elevated temperature increases the response time of the liquid crystal molecules.…”
Section: Optimizing Phase Ripplementioning
confidence: 99%
“…Neural networks are widely used to solve inverse design problems in optics, where trained deep learning models can effectively assist in optical design. Deep learning models, with their powerful processing, recognition, and optimization capabilities, are used in fields such as free-form surfaces [10,11], holographic displays, [12] aberration correction [13], and optical design [14]. This paper proposes an inverse phase modulation method for LC devices based on deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…However, the trade-off with CGH-based metrology is that they are part-specific and often require weeks in lead time for fabrication. To overcome these part-specific limitations of CGH, deformable mirrors (DMs) and spatial light modulators or SLMs are being investigated as adaptive nulls for interferometry [7][8][9][10][11][12] . We have found that DMs typically have a limited wavefront range that they can modulate which is around 50 μm peak-valley (P-V) tilt.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DM-based metrology often requires further additions, such as the Offner null or the tilting of the surface under test (SUT) to measure more significant departures 7 . Recently, Chaudhuri et al developed and reported on an SLM-based reconfigurable interferometric-null test for a freeform surface with 90.6 μm P-V freeform sag over a 65 mm aperture 12 . Using a highdefinition reflective SLM and phase-wrapping, they maximized the wavefront P-V and slope that can be displayed on the SLM and hence enabled the testing of circular aperture freeform optics with about six times larger departures than previously demonstrated SLM-based null tests.…”
Section: Introductionmentioning
confidence: 99%